2016
DOI: 10.1590/18069657rbcs20150091
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobia Isolated from Coal Mining Areas in the Nodulation and Growth of Leguminous Trees

Abstract: An alternative for recovery of areas degraded by coal mining is revegetation with rapidly growing leguminous trees, which often do not establish in low fertility soils. The objective of this study was to evaluate the efficiency of native rhizobia isolated from coal mining areas in the nodulation and growth of leguminous trees. We isolated 19 strains of rhizobia from a degraded soil near Criciúma, SC, Brazil, and evaluated the nodulation and growth-promoting capacity of the inoculated isolates for bracatinga (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
11
0
2
Order By: Relevance
“…In this sense, the use of nitrogen fixing bacteria as an important way to make this nutrient available after the establishment of symbiosis with legumes has been intensively studied. Numerous studies have shown that symbiosis increases N accumulation for many legumes (Calheiros et al, 2013;Moura et al, 2016).…”
Section: Rhizobiamentioning
confidence: 99%
“…In this sense, the use of nitrogen fixing bacteria as an important way to make this nutrient available after the establishment of symbiosis with legumes has been intensively studied. Numerous studies have shown that symbiosis increases N accumulation for many legumes (Calheiros et al, 2013;Moura et al, 2016).…”
Section: Rhizobiamentioning
confidence: 99%
“…Use of quick growing N-fixing plant species in revegetation for restoring degraded coal mine soil could be an effective method by enhancing nutrient cycling, reducing soil erosion, and increasing C assimilation in the soil [5]. N is one of the most important nutrients required for plant growth and development [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, coal mining leads to the elimination of topsoil and vegetation cover, discarding of mine fire, overburden materials, etc. ; this kind of activities cause adverse effects on the physical, chemical, and biological properties of the environment, threatening biodiversity and natural resources [2]. Along with severe land deterioration, coal mining often had detrimental effect on ecosystems [3].…”
Section: Introductionmentioning
confidence: 99%
“…The association between legume species and symbiotic N-fixing bacteria can improve the potentiality of legume species for use in revegetation programs. Their association stimulates increased accumulation of N, decreasing the ratio of soil C/N, which helps mineralization and nutrient cycling, in addition to developing soil organic matter, an essential condition for reclamation of degraded soils [2].…”
Section: Introductionmentioning
confidence: 99%